2022
DOI: 10.1093/cercor/bhab492
|View full text |Cite
|
Sign up to set email alerts
|

Within and beyond the visual cortex: brain tumors induce highly sensitive plasticity of visual processing in whole-brain neural functional networks

Abstract: Vision is a key source of information input for humans, which involves various cognitive functions and a great range of neural networks inside and beyond the visual cortex. There has been increasing observation that the cognitive outcomes after a brain lesion cannot be well predicted by the attributes of the lesion itself but are influenced by the functional network plasticity. However, the mechanisms of impaired or preserved visual cognition have not been probed from direct function-execution conditions and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Although changes in EEG power across frequency bands tend to be most salient in the vicinity of brain tumors, a recent study found that cognition in patients with left frontal gliomas was negatively correlated with beta frequency band connectivity between the contralateral (right) anterior prefrontal and parietal lobules ( Ueda et al, 2022 ). Remote changes in functional connectivity may seem puzzling at first glance, but there is evidence supporting the notion that increased responses and enhanced functional connectivity in regions far from the tumor location may be related to functional compensatory mechanisms ( Yang et al, 2022 ).…”
Section: Applications Of Network and Mapping Techniques To Brain Tumo...mentioning
confidence: 99%
“…Although changes in EEG power across frequency bands tend to be most salient in the vicinity of brain tumors, a recent study found that cognition in patients with left frontal gliomas was negatively correlated with beta frequency band connectivity between the contralateral (right) anterior prefrontal and parietal lobules ( Ueda et al, 2022 ). Remote changes in functional connectivity may seem puzzling at first glance, but there is evidence supporting the notion that increased responses and enhanced functional connectivity in regions far from the tumor location may be related to functional compensatory mechanisms ( Yang et al, 2022 ).…”
Section: Applications Of Network and Mapping Techniques To Brain Tumo...mentioning
confidence: 99%
“…15 Even though prior studies already investigated the functional network of patients with glial brain tumors (GBTs), non-glial lesions and meningiomas, BMs -to the best of our knowledge -have not yet been investigated regarding their impact on the brain's network. [16][17][18][19][20][21][22][23][24][25] GBTs can be roughly subdivided into low-grade gliomas (LGGs) and high-grade gliomas (HGGs), that both derive from neuroepithelial tissue, but differ in terms of malignancy/clinical outcome, growth patterns, molecular signature, and protein expression. 26 Some of these aspects have been previously investigated to identify reasons for network changes in brain tumor patients.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Even though prior studies already investigated the functional network of patients with glial brain tumors (GBTs), non-glial lesions and meningiomas, BMs – to the best of our knowledge – have not yet been investigated regarding their impact on the brain’s network. 16 25 …”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted December 2, 2022. ; https://doi.org/10.1101/2022.12.01.518725 doi: bioRxiv preprint 2019, 2021; Douw et al, 2013;Semmel et al, 2021;van Dellen et al, 2012;van Nieuwenhuizen et al, 2018;Wang et al, 2010a;Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Among adult intraparenchymal brain tumors, brain metastases are the most common, followed by gliomas (Nayak et al, 2012). Even though prior studies already investigated the functional network of patients with glial brain tumors (GBTs), non-glial lesions and meningiomas, brain metastases (BMs) – to the best of our knowledge-have not yet been investigated in regard to their impact on the brain’s network (Bartolomei et al, 2006; Bosma et al, 2009; Derks et al, 2019, 2021; Douw et al, 2013; Semmel et al, 2021; van Dellen et al, 2012; van Nieuwenhuizen et al, 2018; Wang et al, 2010; Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%